Echocardiography in Heart Failure and Cardiac Electrophysiology - Lakshmanadoss, Umashankar (IntechOpen, 2016)
The world of echocardiography continues to be full of exciting new technological developments with an ultimate goal of better patient care. In this book, titled "Echocardiography in Heart Failure and Cardiac Electrophysiology", authors from various parts of the world contributed to the advancement of the field. We have included various chapters about the use of echocardiography and modalities of imaging in various common clinical scenarios - ranging from evaluation of commonly ignored right ventricle, imaging in congestive heart failure, to echocardiographic evaluation of critically ill patients. We have also included topics describing the use of echocardiography in cardiac electrophysiology with special interest to cardiac resynchronization therapy and atrial fibrillation ablation. These topics would be of great interest to the clinicians whether they are trainees, physicians, advanced care providers, or anyone involved in the patient care.